Поліпшення якості медичного обслуговування за допомогою нейромереж - Кушаков, П. К. (ХНУРЕ, 2021)
The use of neural networks in medicine has been made possible by the advent of large amounts of tagged data, as well as markedly increased computing power and the proliferation of cloud storage in all sectors. In medicine, this will have an impact on three levels: for physicians, neural networks help to interpret images quickly and accurately; for health systems - improve workflow, which leads to the potential reduction of medical errors; for patients - allow them to process their own data to promote good health
Keywords: медичне обслуговування; нейромережа